Effect of zirconia on the physicochemical properties of copper (II) imidazolate frameworks - Shaharun, M.S. (American Institute of Physics Inc., 2016)
Copper(II) bis(imidazolate) and copper(II)-zirconia(IV) bimetallic imidazolate were synthesized by metal oxides in aqueous solutions using acid catalyst procedure. The metal imidazolate frameworks were characterized by fourier transform infrared spectra (FTIR), transmission electron microscopy (TEM), ultraviolet-visible spectroscopy (UV-Vis) and N2 adsorption-desorption. The addition of ZrO2 increased the surface area and porosity of the metal organic frameworks. The modification of the copper(II) bis(imidazolate) with addition of ZrO2 enhances the visible light absorbance. The band gap of copper(II)-zirconia(II) bimetallic imidazolate is increased to 2.40 eV with more absorbance in the visible region compared to copper(II) bis(imidazolate). Â© 2016 Author(s).